2x + 2y = 2The answer is Gaussian elimination. This is a relatively straightforward algorithm in which you are permitted three operations on the system:
2x - 2y = -2
- multiplying one row with a scalar variable (i.e., single, real number),
- adding two rows together, or
- exchanging the position of two rows.
Luckily we have a very simple first example.
2x + 2y = 2All we need to do to solve this system is remove 2x from the second row via linear operations, and then substitute the value of y back into the first equation to find x. Here, we use the first and second permitted gaussian operations together: we will add the row 1 (p1), multiplied by the scalar variable -1, to row 2 (p2):
2x - 2y = -2
2x + 2y = 2 (p1)Therefore, if we divide each side by -4, we find that y = 1:
=> -1*2x + -1*2y = -1*2 -1(p1)
=> -2x - 2y = -2 -1(p1)
=>2x - 2x - 2y -2y = -2 - 2 -1(p1)+p2
=> -4y = -4
2x + 2y = 2If we substitute this back into the first equation, we discover that x must equal 0:
y = 1
2x + (2*1) = 2
2x = (2 - 2) = 0
a - c = 0
3a + b = 1
-a + b + c = 4
No comments:
Post a Comment